Experimental study on the interrelation of multiple mechanical parameters in overburden rock caving process during coal mining in longwall panel - Daixin Deng; Hongwei Wang; Lili Xie; Zeliang Wang; Jiaqi Song (International Journal of Coal Science & Technology, 2023)
Abstract In order to comprehend the dynamic disaster mechanism induced by overburden rock caving during the advancement of a coal mining face, a physical simulation model is constructed basing on the geological condition of the 21221 mining face at Qianqiu coal mine in Henan Province, China. This study established, a comprehensive monitoring system to investigate the interrelations and evolutionary characteristics among multiple mechanical parameters, including mining-induced stress, displacement, temperature, and acoustic emission events during overburden rock caving. It is suggested that, despite the uniformity of the overburden rock caving interval, the main characteristic of overburden rock lies in its uneven caving strength. The mining-induced stress exhibits a reasonable interrelation with the displacement, temperature, and acoustic emission events of the rock strata. With the advancement of the coal seam, the mining-induced stress undergoes four successive stages: gentle stability, gradual accumulation, high-level mutation, and a return to stability. The variations in other mechanical parameters does not synchronize with the significant changes in mining-induced stress. Before the collapse of overburden rock occurs, rock strata temperature increment decreases and the acoustic emission ringing counts surges with the increase of rock strata displacement and mining-induced stress. Therefore, the collaborative characteristics of mining-induced stress, displacement, temperature, and acoustic emission ringing counts can be identified as the precursor information or overburden rock caving. These results are in good consistent with on-site situation in the coal mine.